Being a patient: a medical student’s perspective - Rasasingam D; Kerry G; Gokani S; Zargaran A; Ash J; Mittal A (Advances in Medical Education and Practice, 2017)
Dara Rasasingam,1 Georgina Kerry,2 Shyam Gokani,1 Alexander Zargaran,3 Javier Ash,1 Aaina Mittal1 1Department of Medicine, Imperial College School of Medicine, Imperial College London, London, 2Department of Medicine, University of Birmingham Medical School, Birmingham, 3Department of Medicine, St. George’s, University of London, London, UK Abstract: Medical education follows the clinical drive toward patient-centered care and, therefore, puts strong emphasis on the development of empathy by medical students. It has, however, been found that there is a decline in empathy throughout a student’s education. Students’ participation in role-play as the doctor has been proved to improve patient care in a clinical capacity. Here, it is proposed that patient role-play can enhance patient care holistically, by enhancing key communication skills and student’s empathy. Keywords: empathy, role-play, medical education